Comparative viral load analysis of Torque Teno Virus and Torque Teno Mini Virus in COVID-19 infected and non-infected individuals in the United Arab Emirates - Kanu, Gayathri Arumughan; Odeh, Raed Abu; Sekawi, Zamberi; Othman, Zulkefley (Springer Science and Business Media, 2025)
Background: Torque teno virus (TTV) and Torque teno mini virus (TTMV) are highly prevalent, non-pathogenic viruses from the Anelloviridae family that commonly circulate in healthy individuals. Their replication dynamics are closely linked to the host immune status, with viral loads typically increasing during immune suppression or dysregulation associated with viral infections, transplantation, or chronic inflammation. Emerging evidence suggests that TTV may serve as a biomarker of immune competence, with increasing interest in its role during SARS-CoV-2 infection. This study investigated the presence of TTV and TTMV among the study samples, viral load (VL), and demographic associations of TTV and TTMV in COVID-19 infected and non-infected individuals in the United Arab Emirates (UAE). Methods: We analysed 278 plasma samples, 139 COVID-19 infected samples and 139 non-infected samples, via species-specific nested PCR targeting conserved genomic regions downstream of the TATA box in the range of nucleotide positions 99–227 for TTV and 178–303 for TTMV. In-house clones constructed from non-infected COVID-19 samples served as positive controls for the detection and quantification of TTV and TTMV. Real-time qPCR was used to quantify the viral loads. Furthermore, demographic data, including age, BMI, and COVID-19 symptoms, were gathered, and statistically analysed. Results: The TTV-VL was significantly higher in COVID-19 infected individuals (p < 0.001), whereas the TTMV-VL was not significantly different between the groups (p = 0.948). No statistically significant correlation was found between TTV-VL and age or BMI in individual groups, although age-based subgroup analysis revealed notable differences in the co-infected study samples. In co-infected individuals (those harbouring both TTV and TTMV), TTV-VL remained significantly elevated in the COVID-19 infected groups, whereas TTMV-VL remained non-significant. Conclusion: Our findings demonstrate that TTV-VL is elevated in association with COVID-19 infection, suggesting its potential as a marker of immune modulation during SARS-CoV-2 infection. In contrast, TTMV-VL appears to be unaffected by COVID-19 status, indicating different replication dynamics between these related viruses during immune challenge. This study advances our knowledge of the clinical relevance of TTV as a biomarker of immune function and offers the first thorough analysis of anelloviruses viral loads in UAE study samples in the context of COVID-19.